Perancangan Media Informasi Tentang Permainan Tradisional Di Kota Binjai Sumatera Utara - Lubis, Nurul Afifah; Sudiani, Yoni; Rajab, Junaidi (Journal of Tourism Sciences, Technology and Industry, 2024)
Traditional games or folk games in the city of Binjai are part of Indonesian culture that have been passed down from generation to generation. Traditional games contain moral messages that are beneficial for children's motoric, cognitive, emotional and social development. However, as the times progressed which pushed technology in various fields, the existence of traditional games began to be replaced by the presence of modern games which are currently more popular with children. Of course, this has a bad impact, namely that the moral messages and cultural values contained in traditional games are not conveyed well to the next generation, especially children. Therefore, information media is needed to convey these traditional games again. Therefore, 'Designing Information Media About Traditional Games in Binjai City, North Sumatra' was created. This design was made in the form of an illustrated book and several other media mixes. The data collection methods used were observation, interviews, questionnaires, and literature study. In data analysis, the method used is SWOT analysis with a target audience of children aged 7-12 years. Then these data are used in the process of creating the work which goes through several stages. The results of this design become a source of information for the people of Binjai City regarding existing traditional games through a media mix presented in the form of printed illustrated books as the main media. Then there is another media mix which supports the main media consisting of digital book, poster and infographic, traditional games, manual book, merchandise and outdoor media.